Enhancing the Oxford University Research Archive: compliance, consistency, and challenges in supporting researchers - Mitchell, T; Lindgren, T; Partridge, J (Chartered Institute of Library and Information Professionals, 2024)
This paper examines recent developments made to the Oxford University Research Archive (ORA), which has been in place as the University of Oxford's institutional repository, supporting Oxford researchers, since 2007. Over the past four to five years, ORA has undergone significant updates, including the implementation of a new data model, the adoption of enhanced metadata standards, and the integration of automation tools. These changes have streamlined workflows for repository staff by reducing manual tasks, improving metadata consistency, and ensuring compliance with both institutional and external policies, thereby benefiting both researchers and repository administrators. The paper concludes by exploring potential future directions for the continued development of ORA in alignment with emerging researcher needs and policy landscapes.